2018
DOI: 10.14740/jh412w
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Circulating Exosomes Mediated by Surface-Attached Plasma Proteins

Abstract: Background: Exosomes and other types of extracellular vesicles present an important component of circulating plasma. Exosomes released by endothelial and blood cells account for majority of plasma exosomal population; exosomes secreted by other cells might cross tissue-plasma barrier and reach circulating plasma as well. Definitely, exosomes of different cellular origins are different by content and function. However, exosomal surface membrane interacts with plasma components. This interaction may alter compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This study reported 56 common proteins with our proteome from dUC and DG samples, including complement proteins, immunoglobulins, apolipoproteins and keratins. Similar results have also been reported in studies using dUC [31][32][33][34] or SEC as isolation method [35][36][37]. In the study of Karimi et al it was shown that by combining dUC, DG and SEC, it is possible to avoid lipoprotein and soluble protein contamination and to isolate highly purified plasma EVs for proteomic analysis [36].…”
Section: Plos Onesupporting
confidence: 74%
See 1 more Smart Citation
“…This study reported 56 common proteins with our proteome from dUC and DG samples, including complement proteins, immunoglobulins, apolipoproteins and keratins. Similar results have also been reported in studies using dUC [31][32][33][34] or SEC as isolation method [35][36][37]. In the study of Karimi et al it was shown that by combining dUC, DG and SEC, it is possible to avoid lipoprotein and soluble protein contamination and to isolate highly purified plasma EVs for proteomic analysis [36].…”
Section: Plos Onesupporting
confidence: 74%
“…Study samples were collected twice in Helsinki (set I and II) and once in Budapest (set III), the latter to perform fluorescence size exclusion chromatography (Flu-SEC). The average age of the donors in set I was 45 years (range 27-55), 32 years (range 18-51 years) in set II, and 30 years (range [25][26][27][28][29][30][31][32][33][34][35][36] in set III. Majority of the volunteers were females (80%, 70%, and 67%).…”
Section: Preparation Of Plasma and Serummentioning
confidence: 99%
“…Taking into account the obtained data on the concentration of vesicles in CSF, as well as our own experience in visualization of EVs from different biofluids by cryo-EM [20][21][22] we pooled all particle samples (from about 30 mL of CSF for PD patients and 50 mL for the comparison group) for re-ultracentrifugation to maximize the number of EVs in the final pellet. NTA of the sample of vesicles isolated from pooled CSF of PD patients showed that the particles generally varied in size from 26 to 305 nm and that the vesicular size mode, D90 and concentration were 69 nm, 125 nm and 0.6x10 12 particles/ml, respectively ( Fig 1B).…”
Section: Characterization Of Evs By Nta and Flow Cytometry Analysismentioning
confidence: 99%
“…Most exosomes contain proteins that are common among all exosomes regardless of the types of cells which secrete them [ 33 , 34 ]. These characteristic proteins therefore may serve as convenient biomarkers for the isolation and quantification of exosomes.…”
Section: Discussionmentioning
confidence: 99%